WHAT IS INSOMNIA - binti Zaini, Nurzakiah (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Insomnia is a sleep disorder with recurrent difficulty to sleep or maintaining sleep with symptoms tired all day. There are several types of insomnia, transient insomnia which is temporary insomnia, short-term insomnia that can last for several weeks, and chronic insomnia that can last for more than four weeks. Insomnia is caused by several factors, including physical factors such as suffering from certain diseases, environmental factors, psychological factors and psychiatric problems. To overcome this disorder we can use relaxation techniques, subconscious programming, and drug therapy. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: insomnia, sleeping disorder